2019
DOI: 10.1111/jocd.13086
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐skin aging properties of protocatechuic acid in vitro and in vivo

Abstract: Background Protocatechuic acid has reported containing antioxidant effects. However, information on its other biological activities such as anti‐wrinkle properties is limited Aims The objective of this study was to evaluate an antioxidant, collagen synthesis, MMP‐1 inhibition (in vitro), and anti‐wrinkle (in vivo) effects of protocatechuic acid (PCA) as a potent ingredient for wrinkle‐care cosmetic. Methods Antioxidant effect was evaluated based on its scavenging activity for free radicals (DPPH, ABTS+). To ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 24 publications
1
35
0
Order By: Relevance
“…Therefore, as a follow-up of our recent study [ 30 ], in the present work, we were interested in evaluating the ability of BB extracts to prevent O 3 -induced skin inflammasome activation. In addition, BB topical application has been shown to stimulate collagen synthesis and prevent chronological skin aging [ 50 – 52 , 85 ]. Among the wide array of natural antioxidant substances, we decided to focus our attention on blueberries because of their complex phytochemical profiles that have already shown to quench free radicals [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, as a follow-up of our recent study [ 30 ], in the present work, we were interested in evaluating the ability of BB extracts to prevent O 3 -induced skin inflammasome activation. In addition, BB topical application has been shown to stimulate collagen synthesis and prevent chronological skin aging [ 50 – 52 , 85 ]. Among the wide array of natural antioxidant substances, we decided to focus our attention on blueberries because of their complex phytochemical profiles that have already shown to quench free radicals [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed that O 3 was able to decrease both proliferation and migration of the cells while the BB pretreatment prevented these effects probably either via the activation of a cellular defensive system or less probably, by a direct interaction with the free radicals generated by O 3 . It is possible that the inhibition of proliferation is a consequence of their ability to activate NRF2 which has an inhibitory influence on NF- κ B that is one of the regulators of cyclin D1 expression, a key protein for cellular proliferation [ 61 , 85 , 89 ]. Although we did not evaluate the effect of BB on NFR2 activation, we showed a significant decrease in H 2 O 2 by BB after O 3 exposure, although the use of the probe DCF to measure H 2 O 2 is controversial [ 90 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the course of the screening process for potent antiaging biomolecules from food sources, we found that a 50% EtOH extract of Nypa fruticans (NF50E) contained various polyphenolics, including protocatechuic acid, catechin, chlorogenic acid, epicatechin, kaempferol, and a cucurbitane triterpenoid, known as pengxianencin A ( Figure 1(d) ). Among them, protocatechuic acid exhibited not only antiskin aging effects by collagen synthesis and MMP-1 inhibition in vitro but also antiwrinkle effects in vivo [ 24 ]. Protocatechuic acid may be found in various natural sources.…”
Section: Discussionmentioning
confidence: 99%
“…Date seed oil contained a significant phenolic compound and showed diverse pharmacological effects, such as antimutagenic, anticarcinogenic, and anti-inflammatory activities [89,90]. Several phenolic and flavonoid compounds were found in date fruits [91][92][93][94][95][96][97][98][99][100]. Phenolic compounds act as natural antioxidants.…”
Section: Bioactive Compounds From Date Fruits and Seedmentioning
confidence: 99%